Community Engagement and Facilitation in Village Digital Transformation: Leveraging Websites to Enhance MSME Development and Public Information in Kedungdowo Village - Mujiyanti, Sri Ayudha; Suparto, Arico Ayani; Rasidi; Fatoni, Ahmad; Sari, Putri Delila; Hidayat, Rahman; Wardani, Diah Ayu; Lisnawati, Dwi; Qomariyah, Alviyatul; Fadilah, Farhan (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study aims to support the digital transformation of Kedungdowo Village by enhancing the use of its website for public services and the promotion of local potential, particularly MSMEs. Method: The activity employed a participatory approach involving socialization sessions, focused group discussions, and hands-on assistance for village stakeholders. Practical Applications: The program resulted in a structured plan to optimize the OpenSID system, including a domain update and improved content management to promote village resources. Conclusion: The initiative successfully improved digital literacy among village actors and established a model for community-based digital governance in rural areas.